The last letter home - Moberg, Vilhelm, 1898-1973 (Moberg, Vilhelm, 1898-1973. Romanen om utvandrarna., 1995)
From the Publisher: Book Four portrays the Nilsson family during the turmoil of living through the era of the Civil War and Dakota Conflict and their prospering in the midst of Minnesota's growing Swedish community of the 1860s-90s.